Lung endothelial cell-targeted peptide-guided bFGF promotes the regeneration after radiation induced lung injury. (November 2018) - Guan, Dongwei; Mi, Junwei; Chen, Xi; Wu, Yonghui; Yao, Yuanjiang; Wang, Linjie; Xiao, Zhifeng; Zhao, Yannan; Chen, Bing; Dai, Jianwu
Abstract: Basic fibroblast growth factor (bFGF) can protect the lung against radiation-induced pulmonary vascular endothelial apoptosis and subsequent radiation-induced lung injury (RILI). However, guiding bFGF to pulmonary vascular endothelial cells is a key determinant for the success of bFGF therapy. To improve the lung-targeting ability of bFGF, a lung endothelial cell-targeting peptide was fused to bFGF (LET-bFGF). An in vitro biological activity assay indicated that fusion of LET did not affect the bioactivity of bFGF. In addition, the fused protein showed superior lung-targeting ability following intravenous injection. Upon injecting LET-bFGF intravenously after thorax radiation, LET-bFGF could better protect against pulmonary vascular endothelial cell apoptosis as early as 4 h post-radiation. Compared with native bFGF, enhanced therapeutic effects of LET-bFGF were also observed in terms of decreased vascular abnormalities, disorganized lung structure, inflammatory cell migration, and lung density at 2 months post-radiation. Therefore, lung endothelial cell-targeted bFGF may represent a promising remedy for RILI.